INFLUENCE OF STORAGE DURATION ON PHYSICO-CHEMICAL CHANGES IN FRUIT OF APPLE CULTIVARS - I. Jan; A. Rab (Journal of Animal and Plant Sciences, 2012)
The objective of the present research was to study the influence of storage duration on physico-chemical changes in fruit of apple cultivars. The fruits of apple cultivars: Royal gala, Mondial gala, Golden delicious and Red delicious were harvested at optimum maturity and stored for 0, 30, 60, 90, 120 and 150 days in cold storage. The experiment was laid out in Completely Randomized Design (CRD) with twenty four treatment combinations. Physico-chemical changes in fruit were determined at 30 days interval during storage. Apple cultivar Red delicious had the highest juice content (58.47 %), TSS/Acid ratio (23.12), ascorbic acid (13.12 mg/100g), fruit firmness (5.98 kg/cm2), fruit density (0.82 g/cm3) as well as the least weight loss (2.22%) but also had the highest bitter pit (11.86%) and soft rot (13.53%) incidence. Titratable acidity was the highest (0.55%) in cultivar Mondial gala and starch score was the maximum (5.22) in cultivar Golden delicious. The percent weight loss, total soluble solids, total sugar, pH, TSS/Acid ratio, bitter pit incidence and soft rot increased with increase in storage duration while juice content, starch score, titratable acidity, ascorbic acid, firmness and density of fruit declined with increase in storage duration. The results indicated that apple cultivar Red delicious has good quality attributes, whereas cultivar Royal gala has the lowest incidence of bitter pit during prolong storage.
Keywords: Physico-chemical attributes; apple; firmness; weight loss; bitter pit; storage performance; cultivars